PENGARUH KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL PADA PERSISTENSI LABA PERUSAHAAN MANUFAKTUR - Sujana, Made Sujana; YASA, GERIANTA WIRAWAN; BADERA, I DEWA NYOMAN (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study examined the effect of the audit committee and institutional ownership on earnings persistence. This study uses regression analysis techniques (multiple regression) by comparing the coefficient of determination between the two independent variables. The data used in this research is secondary data published on the Stock Exchange using 77 samples of manufacturing firms the period 2011-2012. The analysis showed that audit committees have negative effect on the persistence of earnings, while institutional ownership has a positive effect on earnings persistence. The audit committee has a negative effect on earnings persistence may be caused by the greater number of the audit committee are owned by the persistence of earnings will tend to decline . Institutional ownership has a positive effect on earnings persistence implies that the greater number of shares owned by institutional shareholders, the persistence of earnings will tend to increase .